Human biomonitoring as a tool for exposure assessment in industrially contaminated sites (Icss). lessons learned within the ics and health european network - Colles, Ann; Ardeleanu, Elena-Roxana; Candeias, Carla; Ranzi, Andrea; Demeter, Zoltán; Hofer, Adam; Kowalska, Malgorzata; Makris, Konstantinos C.; Arrebola, Juan Pedro; Hough, Rupert Lloyd; Pérez-Carrascosa, Francisco Miguel; Iavarone, Ivano; et al. (My University, 2019)
BACKGROUND: the mixed and complex nature of industrially contaminated sites (ICSs) leads to heterogeneity in exposure and health risk of residents living nearby. Health, environment, and social aspects are strongly interconnected in ICSs, and local communities are often concerned about potential health impact and needs for remediation. The use of human biomonitoring (HBM) for impact assessment of environmental exposure is increasing in Europe. The COST Action IS1408 on Industrially Contaminated Sites and Health Network (ICSHNet) decided to reflect on the potential and limitations of HBM to assess exposure and early health effects associated with living near ICSs. OBJECTIVES: to discuss challenges and lessons learned for addressing environmental health impact near ICSs with HBM in order to identify needs and priorities for HBM guidelines in European ICSs. METHODS: based on the experience of the ICSHNet research team, six case studies from different European regions that applied HBM at ICSs were selected. The case studies were systematically compared distinguishing four phases: the preparatory phase; study design; study results; the impact of the results at scientific, societal, and political levels. RESULTS: all six case studies identified opportunities and challenges for applying HBM in ICS studies. A smart choice of (a combination of) sample matrices for biomarker analysis produced information about relevant time-windows of ex posure, which matched with the activities of the ICSs. Combining biomarkers of exposure with biomarkers of (early) biological effects, data from questionnaires or environmental data enabled fine-tuning of the results and allowed for more targeted remediating actions aimed to reduce exposure. Open and transparent communication of study results with contextual information and involvement of local stakehold ers throughout the study helped to build confidence in the study results, gained support for remediating actions, and facilitated sharing of responsibilities. Using HBM in these ICS studies helped in setting priorities in policy actions and in further research. Limitations were the size of the study population, difficulties in recruiting vulnerable target populations, availability of validated biomarkers, and coping with exposure to mixtures of chemicals. CONCLUSIONS: based on the identified positive experiences and challenges, the paper concludes with formulating recommendations for a European protocol and guidance document for HBM in ICS. This could advance the use of HBM in local environmental health policy development and evaluation of exposure levels, and promote coordination and collaboration between researchers and risk managers.
Biomonitoraggio umano come strumento per valutare l’esposizione nei siti industriali contaminati. Lezioni apprese dal network europeo icshnet
Keywords: Biomarkers; Human biomonitoring; Human exposure; Industrially contaminated sites; Study design